The Effect of Bank Soundness Level on Dividend Policy Using the RGEC Method in the Banking Sector Listed on the Indonesia Stock Exchange - Gita Terawati; Dian Safitri Pantja Koesoemasari; Harsuti Harsuti (Darul Yasin Al Sys, 2026)
This study examines the effect of credit risk, liquidity risk, Good Corporate Governance (GCG), earnings, and capital on dividend policy, proxied by the Dividend Payout Ratio (DPR), among banking firms listed on the Indonesia Stock Exchange during the 2020–2024 period. The study is motivated by inconsistent empirical findings on the determinants of dividend policy, particularly in the banking sector, which operates under strict regulatory frameworks and has financial structures that differ from those of other industries. This study aims to analyze the effect of each determinant on dividend policy and identify the dominant factor influencing DPR. A quantitative approach was employed using panel data regression analysis. The sample consisted of banking firms listed on the Indonesia Stock Exchange during the study period. The analysis applied the Common Effect Model, Fixed Effect Model, and Random Effect Model, with model selection determined through the Chow and Hausman tests. Classical assumption testing and statistical significance testing were also conducted to ensure model validity and robustness. The findings show that, partially, only the Loan to Deposit Ratio (LDR) has a positive and statistically significant effect on DPR. In contrast, Non-Performing Loan (NPL), GCG, Return on Assets (ROA), and Capital Adequacy Ratio (CAR) do not have statistically significant effects on dividend policy. However, the simultaneous test indicates that all independent variables jointly have a significant effect on DPR. These findings suggest that dividend policy in the banking sector is primarily driven by intermediation efficiency and liquidity management rather than by risk exposure, governance mechanisms, profitability, or capital adequacy. This study concludes that liquidity is the key determinant of dividend policy in Indonesian banking firms. The study contributes to the literature on dividend policy determinants in regulated financial institutions and provides practical implications for bank management and investors by emphasizing liquidity indicators as critical considerations in dividend policy formulation and investment decision-making.